Effectiveness of a Multimodal E-Book in Enhancing 21st Century Skills in Pancasila Education - Dharma, Surya; Hodriani; Halking; Safitri, Ira (Universitas Islam Negeri Raden Fatah Palembang, South Sumatra, Indonesia, 2026)
The weakening of students' civic character is caused by the influence of globalization and the ineffectiveness of conventional learning methods in Pancasila Education. These challenges demand innovative learning media that can foster 21st-century skills while internalizing Pancasila values. This study aims to develop and test the effectiveness of Multimodal E-Books as a learning medium capable of improving students' critical thinking and collaboration skills. A mixed method with a Research and Development (R&D) approach followed by a quasi-experiment was used in this study. The e-book was tested on two groups of students, namely the experimental group and the control group, with 30 participants in each group. This study included expert validation, pre-test, post-test, normality test, homogeneity test, independent sample test, and N-Gain analysis. The results show that the Multimodal E-Book is highly valid and suitable for use. In the effectiveness test stage, the experimental group obtained an N-Gain score of 0.68, which falls into the medium-high category. Meanwhile, the control group obtained an N-Gain score of 0.32, which falls into the low-medium category. The t-test results confirm that the difference between the two groups is highly significant (sig. 0.000). This study concludes that Multimodal E-Books are effective as a transformative learning medium capable of improving critical and collaborative skills and understanding of Pancasila values among students.